Perancangan Aplikasi Pengarsipan Surat Menyurat Subbagian Fraksi Gerindra DPRD Provinsi Sumatera Utara - Tasya Ika Saylani Tarigan; Mutammim Zisdian (Asosiasi Riset Teknik Elektro dan Informatika Indonesia, 2025)
This research discusses the design of correspondence filing applications at the Subdivision of the Gerindra Faction of the North Sumatra Provincial DPRD. The letter filing system that is still done manually causes various obstacles such as difficulty in finding documents, the risk of damage and loss of physical documents, and inefficiency in archive management. The purpose of this research is to design a computer-based application to optimize the process of filing incoming letters and outgoing letters. The system development method used is waterfall with the stages of needs analysis, system design, implementation, and testing. The application is designed using PHP programming language and MySQL database to store mail data. The results showed that the designed application can facilitate the process of archiving, searching, and managing correspondence digitally and increase work efficiency in the Gerindra Faction Subdivision of the North Sumatra Provincial DPRD. This system is also equipped with a security feature in the form of a user login to maintain document confidentiality.